DNA variation at the Sod locus of Drosophila melanogaster: An unfolding story of natural selection - Hudson, Richard R. (The National Academy of Sciences of the USA, 1997)
Patterns of variation at the Sod locus of Drosophila melanogaster suggest that the protein polymorphism at this locus has very recently arisen. In addition, it appears that a previously rare DNA variant has been recently and rapidly driven to intermediate frequency. From the size of the region (>20 kb) that has been swept along with this rare variant, and patterns of linkage disequilibrium in the region, it is inferred that strength of selection was large (s > 0.01) and that the sweep occurred more than 25,000 generations ago. In addition, there are striking similarities to patterns of variation observed at the Est6 and Est-P loci, which are located approximately 1,000 kb from Sod.